2018
DOI: 10.1016/j.ejbas.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total phenols, flavonoids and antioxidant potential of local and imported ripe bananas

Abstract: Bananas are globally used trade crops for nutrition and traditional medicine. The following research aims to study different polarity banana extracts from local and imported ripe bananas and determine the amount of phenols and flavonoids contents, and antioxidant potential by applying various spectroscopic methods. The banana extracts were prepared from the powdered banana samples of Pilipino (Cavendish) and Salalah ripe banana (Somali) by the maceration method with methanol. The methanol extracts were suspend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
3
31
0
2
Order By: Relevance
“…Phenolic compounds are secondary metabolites of plant origin that possess biological activity [8]. In kombucha, they are believed to be a product of hydrolysis of a polyphenolic compounds originating from the herbal raw material [30].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds are secondary metabolites of plant origin that possess biological activity [8]. In kombucha, they are believed to be a product of hydrolysis of a polyphenolic compounds originating from the herbal raw material [30].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…known as the source of natural antioxidant compounds [8]. Nitrogen compounds are not characteristically part of medicinal herb composition.…”
mentioning
confidence: 99%
“…The solvent was concentrated in vacuo at reduced pressure and temperature (40°C) to obtain the corresponding extracts (9.7 g). The dried extract (7 g) was dissolved in water (200 ml) by using sonication and prepared different fraction by different polarities of solvent starting from nonpolar solvent through successive fractionation [13]. All separated fractions were evaporated at reduced pressure and temperature (40°C) to obtain the corresponding extracts (hexane (1.09 g), chloroform (1.99 g), ethyl acetate (2.17 g) and butanol (0.839 g).…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Flavonoids have important positive effects on human health especially due to their antioxidant and free radical scavenging. Although several studies have shown that some flavonoids have a pro-oxidant effect, they only occur at high doses, most of which confirm the existence of anti-inflammatory effects, antiviral or anti-allergic, and their protective role against cardiovascular disease, cancer, and various pathologies [2,4].…”
Section: Introductionmentioning
confidence: 99%